Effect of Drying Methods on Chemical Composition of Spinach “Aieifo” (Amaranthus aquatica) and Pumpkin Leaf (Telfairia occidentalis) and Their Soup Meals - Gladys, H.E. Oguche (Pakistan Journal of Nutrition, 2011)
The study evaluated the effect of drying; methods on chemical composition of spinach, “aleifo” (Amaranthus aquatica) and pumpkin leaf (Telfairia occidentalis) and their soup meals. The two vegetables were purchased from local market in Unale-Ibaji Local Government Area, Kogi State, Nigeria in bulk. These two vegetables were washed, cleaned, plucked from the stalk and processed to mimic traditional methods of preserving vegetables. The vegetables were divided into three equal portions. The first portion served as the control, the second and third portions were sun and shade dried. Aliquots of the dried samples were pulverized, sieved, packaged in polythene bags and kept in cool dry place until used for various chemical analysis. The other dried portions as well as their controls (fresh) were used for preparation of soup meals. The chemical composition of the vegetables and their soup meals were determined using current standard methods. Sun and shade drying drastically reduced moisture content of the vegetables when compared to the controls (84.47-7.80 and 7.42%). The protein for the sun and the shade dried samples were higher than those of the controls (3.50 and 4.70 vs 6.47, 5.50 and 5.77 and 5.44%, respectively) (p<0.05). Ash, fat and fibre content of the dried samples were also higher. Carbohydrate values for the two vegetables were slightly high and comparable (47.36 and 48.40%) than those of the controls. Calcium, iron and zinc of the fresh samples were higher than those of the dried samples. Drying comparably increased energy from 131.37- 198 and 197 kcal, each. Drying increased iodine and decreased β-carotene and ascorbate as against the controls. Drying equally decreased phytate and tannins relative to their controls. The moisture values for soup prepared with dried vegetables were lower than those prepared with fresh vegetables. The dry matter (protein, fat, ash and carbohydrate) for the soups prepared with dried vegetables were much higher than those prepared with fresh vegetables. On the other hand, calcium, iron, zinc and iodine values for soups prepared with fresh vegetables were higher than those prepared with fresh vegetables were higher than those prepared with dried vegetables. Phytate and tannins values for soups based on dried vegetables were lower than those based on fresh vegetables. Fresh vegetables had higher iron, vitamin A and ascorbate than the dried vegetables. Shade drying had an edge in increasing iron, iodine, zinc, pro-vitamin A and ascorbate over sun drying. However, sun drying lowered phytate and tannins more than shade drying. Shade drying is a better drying method to preserve and retain nutrient in these two green leafy vegetables.